Monofunctional epoxy-POSS dispersed in epoxy - Amine networks: Effect of a prereaction on the morphology and crystallinity of POSS domains - Zucchi, Ileana Alicia (2007)
Several studies have recently reported the use of monofunctional octahedral oligomeric silsesquioxanes (monofunctional POSS) to modify polymer networks. In most of these studies the final material is depicted as a network with pendent POSS units randomly dispersed in the structure. The aim of this paper is to show that this representation is generally not correct due to the occurrence of a polymerization-induced phase separation (PIPS) process. In this sense, monofunctional POSS are not different from different types of rubbers, thermoplastics, or liquid crystals used to modify polymer networks. Although some authors have noticed the occurrence of PIPS in particular systems, a comparative study of the effect of the chemical structure of POSS and its prereaction with one of the monomers on the morphologies generated has not been previously reported. Glycidyloxypropyl-heptaisobutyl POSS (iBu-GlyPOSS) and glycidyloxypropyl-heptaphenyl POSS (Ph-GlyPOSS) were used to modify an epoxy network based on diglycidyl ether of bisphenol A (DGEBA) and 4,4′-methylenebis(2,6-diethylaniline) (MDEA). POSS was introduced in the formulation either nonreacted or prereacted with MDEA (molar ratio POSS/MDEA: 1/10). While both nonreacted and prereacted iBu-GlyPOSS were soluble in the epoxy - amine precursors at the polymerization temperature (135°C), only prereacted Ph-GlyPOSS could be dissolved in epoxyamine precursors. For every case a polymerization-induced phase separation took place. For the nonreacted iBuGlyPOSS this process led to a dispersion of spherical particles with sizes in the range of the micrometers that crystallized upon cooling. Both prereacted POSS led to different types of amorphous biphasic structures. Therefore, the nature of the organic inert group and the prereaction of a monofunctional POSS can be used to control the morphologies generated in the POSS-modified polymer network.